2013
DOI: 10.1111/medu.12334
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism and social media: an interprofessional learning activity

Abstract: What problem was addressed? Medical educators must help future doctors develop a professional identity that supports teamwork, including appropriate development of knowledge-, attitude-and skill-based competencies required to perform optimally on teams. Unfortunately, despite being presented multiple opportunities to work in teams, learners do not always develop team-focused competencies. Importantly, many fail to develop a team-level orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Students who have used social media for many years may feel that studying social media communication skills is not relevant to their dental education and does not need to be addressed in an educational setting. This tendency to discount the need for structured learning in an area in which students believe they have the upper hand over faculty showcases the notion of unconscious incompetence 57 …”
Section: Transition To Health Professions Studentmentioning
confidence: 99%
“…Students who have used social media for many years may feel that studying social media communication skills is not relevant to their dental education and does not need to be addressed in an educational setting. This tendency to discount the need for structured learning in an area in which students believe they have the upper hand over faculty showcases the notion of unconscious incompetence 57 …”
Section: Transition To Health Professions Studentmentioning
confidence: 99%
“…52,54 Even though students understood the need for professionalism when using SoMe for medical education, 49,93,107,125,132,133,134 they appreciated educational interventions with regards to this. 40,56,135,136 Studies suggested privacy concerns were a barrier to effective SoMe use 47,64,69 but closed SoMe groups or bespoke networks may alleviate such concerns. 53,74 This does, however, limit global interactions 53 and only three studies identified accessing expertise from around the world as an advantage.…”
mentioning
confidence: 99%
“…26 Several opinion articles also referred to the incorporation of teaching on professional use of social media, including obstacles that may be encountered, eg the high risks of exploratory learning. 8,43,46,48…”
Section: Author(s)mentioning
confidence: 99%
“…Abdelkarim and Sullivan 25 Arnett et al 31 Beebe et al 0 Brown 34 Jorgensen 38 De Groote et al 27 Gonzalez and Gadbury Amyot 23 Haas and Park 33 Hamm et al 32 Hatch et al 46 Hughes 37 Khatoon et al 24,29 Kothari et al 22 Levin 39 McAndrew and Johnston 47 Meerschaert 40 Perel 58 Risk 41 Snyman and Visser 28 Spallek et al 43 Stein et al 45 Hancocks 54 Oakley and Spallek 48 Peltier and Curley 55 Roucka et al 52 Affleck and Macnish 50 Chan 57 Drone 35 Foster 53 Henry and Pieren 26 Henry 36 Khatoon et al 44 Mc Crory and Jacobs 5 Neville and Waylen 51 Parkinson and Turner Schafer 56 Spallek et al 42…”
mentioning
confidence: 99%